2009
DOI: 10.3892/ijmm_00000155
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variants in interleukin-6 modified risk of obstructive sleep apnea syndrome

Abstract: Abstract. Obesity and inflammation are known to correlate with the pathogenesis of obstructive sleep apnea syndrome (OSAS). Interleukin (IL)-6, an important regulator of obesity and inflammation, was reported to phenotypically increase in patients with OSAS. This study aimed to investigate whether genetic variants in IL-6 confer susceptibility to OSAS. The study population consisted of 151 patients with OSAS and 75 healthy controls from Southeast China. Five haplotype-tagging single nucleotide polymorphisms (t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 36 publications
(48 reference statements)
3
17
0
Order By: Relevance
“…According to Zhang et al, a polymorphism found in the promoter region of IL6 gene (−G174C) affects its gene expression. A similar role in the metabolism of the adipose tissue was also attributed to TNF-α where its levels also depend on the presence of a polymorphism (-G308A) in the promoter region of TNFA [58]. The presence of the A allele can double the expression of this gene, leading to a higher production of TNF-α.…”
Section: Association Studies Of Inflammatory Response Genes and Osasmentioning
confidence: 87%
See 1 more Smart Citation
“…According to Zhang et al, a polymorphism found in the promoter region of IL6 gene (−G174C) affects its gene expression. A similar role in the metabolism of the adipose tissue was also attributed to TNF-α where its levels also depend on the presence of a polymorphism (-G308A) in the promoter region of TNFA [58]. The presence of the A allele can double the expression of this gene, leading to a higher production of TNF-α.…”
Section: Association Studies Of Inflammatory Response Genes and Osasmentioning
confidence: 87%
“…The presence of the A allele can double the expression of this gene, leading to a higher production of TNF-α. Thus, it is possible to infer that the influence of the lipid metabolism and the energetic expenditure is linked to the concentration of these cytokines, which might contribute to weight gain in OSAS [42], being also a common risk factor for obesity and metabolic disturbances, especially insulin resistance [58].…”
Section: Association Studies Of Inflammatory Response Genes and Osasmentioning
confidence: 99%
“…However, the minor allele 'G' (rs1800796) decreased the risk of OSAS in non-obese subjects, compared with the major allele 'C' (OR, 0.48; 95% CI, 0.26-0.86; P=0.014). We believe it is primarily attributed to the different definition for overweight or obese patients (BMI ≥25 vs. ≥27 kg/m 2 ), and in addition, subgroup analysis was not conducted according to the severity of disease in the Zhang et al (24) study.…”
Section: Male N (%) Female N (%) ----------------------------------mentioning
confidence: 99%
“…These differences were ascribed to the distinct genetic background and the different living environments of the Chinese population compared with other ethnicities. Zhang et al (24) identified that no distribution difference in the IL-6 gene was observed between OSAS patients and controls in the Chinese Han population. However, the minor allele 'G' (rs1800796) decreased the risk of OSAS in non-obese subjects, compared with the major allele 'C' (OR, 0.48; 95% CI, 0.26-0.86; P=0.014).…”
Section: Male N (%) Female N (%) ----------------------------------mentioning
confidence: 99%
“…IL-6 is a pleiotropic cytokine of 23.7 kDa secreted by many cells of the immune system, cardiovascular components and adipose tissue, and functions as a mediator of inflammatory response with both pro-and anti-inflammatory properties (8). Circulating levels of IL-6 differ greatly between individuals (8,9), due to genetic and environmental factors (10).…”
Section: Introductionmentioning
confidence: 99%